Validity and Legal Consequences of Peace Agreements in The Settlement of Sexual Harassment Cases - Rahayu, Hartoto Suci; Markoni; Dyah Permata Budi Asri; I Made Kanthika; Tuti Elawati (Dinasti Research, 2026)
The settlement of sexual harassment cases through peace agreements based on contracts remains a practice commonly found in society. This practice raises complex legal issues as it lies at the intersection of civil law and criminal law. On one hand, civil law recognizes contracts as legally binding instruments provided that the legal requirements of validity are fulfilled. On the other hand, sexual harassment constitutes a criminal offense, meaning that its resolution cannot rely solely on the agreement of the parties involved. This study aims to analyze the settlement of sexual harassment cases through contractual peace agreements from the perspectives of civil law and criminal law. The research employs a normative legal method using statutory and conceptual approaches. The legal materials consist of primary and secondary sources, which are analyzed qualitatively. The findings indicate that peace agreements in sexual harassment cases may be considered legally valid only if they fulfill the legal requirements of a contract, particularly the existence of free consent and a lawful cause. From a criminal law perspective, a peace agreement between the perpetrator and the victim does not eliminate the unlawful nature of sexual harassment, as such acts involve public legal interests protected by the state. Therefore, peace agreements may only operate within the civil law domain and cannot be used as a basis to negate criminal law enforcement processes.